DETERMINANTS OF SERVICE QUALITY: Efficiency and Workspace - Munarko, Anggi (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
Building quality education requires great effort and sacrifice, not only aspects of human resources, but other aspects such as infrastructure, services, management systems, and so on need to be considered. These things become a necessity and fundamental, so that all parties involved are obliged to strive. The purpose of this study is to reveal information about the factors that may improve employee performance and service quality. The research method uses quantitative with statistical regression analysis and the sampling technique uses stratified simple random. The data source is BBPMPPV Business and Tourism employees of the Ministry of Education and Culture of West Java, totaling 70 people. The research data was obtained through the distribution of online questionnaires (using google forms). The results of the study reveal that the efficiency in question is a simple work process without long bureaucracy, so as to be able to provide excellent service. As for the workspace layout, it can make it easier for service users to be able to know/recognize the services provided. Either simultaneously or partially, design and efficiency can improve employee service performance.